Effects of Chenpi Jiaosu on serum metabolites and intestinal microflora in a dyslipidemia population: a randomized controlled pilot trial - Tan, Fei; Zheng, Yuying; Wang, Chengcheng; Huang, Jiaying; Liu, Xin; Su, Weiwei; Chen, Xinyan; Yang, Zhimin (Frontiers in Endocrinology, 2025)
IntroductionDyslipidemia is a critical risk factor for atherosclerosis and cardiovascular/cerebrovascular events, necessitating effective long-term management. However, conventional lipid-lowering drugs such as statins and fibrates are limited by adverse effects, including hepatotoxicity and myopathy, which restrict their prolonged use. Traditional Chinese medicine (TCM) and natural health products offer potential alternatives with multi-target mechanisms and improved safety profiles. Tangerine Peel Enzyme Drink (CPJS), a fermented health product derived from tangerine peel, has demonstrated lipid-modulating properties. This study aimed to evaluate the efficacy and safety of CPJS in improving dyslipidemia and explore its underlying metabolic and microbiological mechanisms.MethodsA randomized, double-blind, parallel-controlled clinical trial was conducted with 72 participants (55 completers). Participants were divided into CPJS and control groups, receiving an 8-week intervention. Primary outcomes included changes in body weight and serum triglycerides (TG), while safety was assessed via liver/kidney function, creatine kinase, blood, and urine tests. Serum metabolomics (93 differential metabolites identified) and intestinal microbiota analysis were performed to elucidate metabolic pathways and microbial shifts. KEGG enrichment analysis mapped metabolites to biological pathways, such as lipid and amino acid metabolism.ResultsThe CPJS group exhibited significant reductions in body weight and TG levels post-intervention (p < 0.05), with no adverse effects observed in safety biomarkers. Metabolomic profiling revealed alterations in fatty acyl, glycerophospholipid, and organic acid metabolites, indicating CPJS modulates lipid metabolism and energy homeostasis. KEGG analysis linked these changes to pathways including triglyceride degradation and amino acid metabolism. Additionally, CPJS increased specific gut microbial taxa associated with lipid regulation, suggesting a microbiome-mediated mechanism.DiscussionCPJS demonstrates efficacy in improving dyslipidemia through dual mechanisms: direct modulation of triglyceride metabolism and indirect regulation via gut microbiota. Its safety profile aligns with findings from natural products like Cyclocarya paliurus and tempeh, which mitigate lipid abnormalities without hepatotoxicity. The multi-target action of CPJS mirrors TCM principles, where compounds like quercetin and flavonoids in CPJS may synergistically inhibit cholesterol synthesis and enhance lipid clearance. However, further research is needed to isolate active components and validate microbial contributions. Compared to synthetic drugs, CPJS offers a safer adjunct therapy, addressing limitations of current pharmacotherapies. Future studies should explore dose-response relationships and long-term outcomes in diverse populations.